Desenvolvimento de um sistema de iluminação inteligente para motocicletas - Dias, Igor Huchberg (2012)
This project describes the development of an intelligent headlamp control system for motorcycles, illuminating the curves according to the inclination of the motorcycle. An angular rate sensor (gyro) was utilized for this, along with two servomotors and a HID (High Intensity Discharge) lighting system. The system goal is to obtain a light beam always parallel to the horizontal plane and the horizontal angle that varies according to the tilting motion of the motorcycle, improving visibility on bends. For this a servomotor was utilized that rotates the headlamp keeping the light beam always parallel to the horizontal plane regardless of the variation of the motorcycle inclination. A second servomotor was used to perform the horizontal angle variation of the lighting beam. The angular rate sensor performs the current reading of the angular rate of the motorcycle and delivers this information to the microcontroller board Arduino Duemilanove. The communication between the angular rate sensor and the microcontroller is provided by a module in the sensor board that allows the conversion of the analogical data into digital data and provides this information to the microcontroller via the I2C interface. For programming and code debug the Arduino development environment was utilized. The tests were performed with a prototype designed specially for this, allowing the angular motion of a still motorcycle, simulating the motorcycle inclination in a curve. Placing the prototype against the wall, at a stipulated distance, allowed the making of adjustments in the system and see the results. Based in the tests performed, the results were considered satisfactory as they met the general objective.